Moments of Pleasure: A Preliminary Classification of Gustatory mmms and the Enactment of Enjoyment During Infant Mealtimes - Wiggins, Sally (Frontiers in Psychology, 2019)
The enjoyment of food and the sharing of mealtimes is a normative cultural and social practice. Empirical research on eating enjoyment has, however, been a rather neglected area across the social sciences, often marginalized in favor of health or focusing on individual preferences rather than shared enjoyment. Even with regards to children, their enjoyment of food is typically rated retrospectively via parental reports of mealtime behavior. What is missing is an understanding of how enjoyment becomes a normative, cultural practice during mealtimes. This paper examines this issue in the context of parents feeding their five- to eight-month-old infants in the family home, since it is within this context that we can see the early emergence of normative practices in often highly routinized situations. The enactment of eating as enjoyable, and of the food as appreciated or ‘liked’ in some way, is a culturally normative practice that becomes recognizable through particular non-lexical (‘mmm’, ‘ooh’) or lexical (‘this is nice, isn’t it?’) utterances. The data comprise 66 infant mealtimes video-recorded over almost 19 hours, from five families living in Scotland. The analysis uses discursive psychology and focuses on the sequential position of different types of parental gustatory mmms as produced during the infant meals. A classification of four types of mmm were identified in the corpus – announcement, receipting, modelling and encouragement mmms - each associated with features of sequential and multimodal organization within the mealtime. In the majority of instances, mmms were uttered alone with no other assessment terms, and parents typically produced these as an orientation to the enjoyment of their infants’, rather than their own, eating practices. The receipting mmms, for instance, occurred at the precise moment when the infant’s mouth closed around the food. It is argued that eating enjoyment can be considered as much an interactional practice as an individual sensation, and that non-lexical vocalizations around food are an essential part of sensory practices. The paper thus aims to bridge the gap between cultural and psychological studies of eating enjoyment and contribute to developmental studies of infant feeding in everyday interaction.